Formaldehyde exposure alters miRNA expression profiles in the olfactory bulb. (July 2015) - Li, Guifa; Yang, Jing; Ling, Shucai
Abstract It has been reported that inhaling formaldehyde (FA) causes damage to the central nervous system. However, it is unclear whether FA can disturb the function of the olfactory bulb. Using a microarray, we found that FA inhalation altered the miRNA expression profile. Functional enrichment analysis of the predicted targets of the changed miRNA showed that the enrichment canonical pathways and networks associated with cancer and transcriptional regulation. FA exposure disrupts miRNA expression profiles within the olfactory bulb.